The global prevalence of sexual dysfunction in women with multiple sclerosis: a systematic review and meta-analysis - Salari, Nader; Hasheminezhad, Razie; Abdolmaleki, Amir; Kiaei, Aliakbar; Razazian, Nazanin; Shohaimi, Shamarina; Mohammadi, Masoud (Springer Science and Business Media LLC, 2022)
Background: Sexual function is often impaired following neurological disorders such as multiple sclerosis (MS). Young women with MS encourage disruptions in sexual function, sexual behaviors, and family formation as common global problems. Thus, the aim of the present systematic review and meta-analysis study was to investigate the global prevalence of female sexual dysfunction (FSD) worldwide. Methods: Various databases (PubMed, Scopus, Web of Science, Embase, and ScienceDirect) along with Google Scholar search engine were hired for systematic searching in the field of the prevalence of FSD (by July 2022). The heterogeneity of the studies was assessed using I2 index, and random effects model was used to perform the analysis (CMA software, v.2). Results: Following assessment of 14 included studies with the sample size of 2115 women, a total prevalence of sexual dysfunction (SD) in women with MS was reported 62.5 (95 CI 53.9–70.5). Meta-regression assessment also showed that FSD accelerates following increasing the sample size and the year of the studies. Conclusion: The total prevalence of SD in women with MS was found considerably high (62.5) in the world, which needs more serious attention by health policymakers. Correct implementation of health policies can potentially increase the society’s awareness and successful treatment of SD in MS patients